Prinsip - Prinsip Blockchain Berbasis Transparansi, Keamanan dan Immutability : Studi pada Eksistensi Aplikasi Byond By Bank Syariah Indonesia (BSI) - Helen Purnamasari; Andang Sunarto; Padlim Hanif (Tasyri' : Jurnal Muamalah dan Ekonomi Syariah, 2026)
This study aims to analyze the role of blockchain principles, namely transparency, security, and immutability, as an analytical framework for understanding user trust and users' perceptions regarding the existence of the Byond application by Bank Syariah Indonesia (BSI). This qualitative study employed a case study approach involving one Bank Syariah Indonesia employee and six active Byond users selected through purposive sampling. The research was conducted at Bank Syariah Indonesia KC Bengkulu Adam Malik using observation, in-depth interviews, and documentation as data collection techniques. Data were analyzed through data reduction, data display, and conclusion drawing. The findings indicate that users perceive transparency as reflected in transaction information and service openness, although several transaction details still require improvement. Security is perceived through multi-layer authentication, identity verification, and user data protection, while immutability is reflected in the perceived integrity and consistency of transaction records that strengthen users' confidence in digital banking services. Overall, users perceive these three principles as supporting trust and reinforcing the existence of the Byond application amid competition in digital banking services. This study is limited to users' perceptions within a single case study and does not examine the technical implementation of blockchain infrastructure in the Byond application.